PH-responsive starch-based gel coated slow-release fertilizer

By converting ordinary corn starch into amorphous starch, and performing a cross-linking polymerization reaction with acrylic acid and a cross-linking agent, a pH-responsive starch-based gel coating is formed, which solves the problem of pH-responsive starch-based hydrogel coating in the existing technology. The problem of insufficient research on glue has been solved, and the intelligent control and efficient slow-release effect of fertilizer nutrient release rate have been achieved.

CN119350094APending Publication Date: 2025-01-24LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411451729.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, there are few studies on starch-based hydrogels with pH responsiveness, and it is impossible to effectively control the nutrient release rate of fertilizers in different pH environments, which limits its development as a slow-release fertilizer coating material.

Method used

Through a specific preparation process, ordinary corn starch is converted into amorphous starch, and cross-linked and polymerized with acrylic acid (AA) monomer and cross-linking agent N, N'-methylene bisacrylamide (MBA) to form A pH-responsive starch-based gel coating with a three-dimensional network structure is coated on the surface of the core fertilizer to control the release rate of nutrients.

Benefits of technology

Intelligent adjustment of nutrient release rates based on changes in soil pH, improves the pH response and slow -release performance of fertilizer, and significantly improves the utilization rate of fertilizers and environmental protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350094A_ABST
    Figure CN119350094A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fertilizers, and discloses a pH-responsive starch-based gel coated slow-release fertilizer, which comprises a core fertilizer and a pH-responsive starch-based gel coating coated on the surface of the core fertilizer, and is characterized in that the core fertilizer is urea, and a coating material is prepared from amorphous starch, an acrylic acid (AA) monomer and a cross-linking agent N, N-dimethylformamide. The polymer is prepared from N, N '-methylene bisacrylamide (MBA) and an initiator potassium persulfate (KPS) through a cross-linking polymerization reaction. Through a specific preparation process, common corn starch is converted into amorphous starch, the amorphous starch is successfully cross-linked with an acrylic acid (AA) monomer and a cross-linking agent N, N '-methylenebisacrylamide (MBA) to form the pH-responsive starch-based gel with a three-dimensional network structure, and the permeability of the gel can be intelligently adjusted according to the change of the pH value of soil, so that the pH-responsive starch-based gel can be applied to the field of soil remediation. Therefore, rapid release of nutrients in acid soil is promoted, release of nutrients in alkaline soil is slowed down, and the pH responsiveness of the fertilizer is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fertilizers, in particular to a pH-responsive starch-based gel-coated slow-release fertilizer. Background Art

[0002] Traditional fertilizers often have problems such as too fast nutrient release, low utilization rate, and easy soil and water pollution after application. In order to solve these problems, people have developed a variety of slow-release fertilizers. Starch-based gel-coated slow-release fertilizers are slow-release fertilizers prepared using starch and its derivatives as coating materials. The fertilizer uses a specific process to modify starch or compound it with other materials to form a coating layer with slow-release function, which is wrapped on the surface of fertilizer particles, thereby achieving the purpose of controlling the fertilizer nutrient release rate and extending the service life of the fertilizer.

[0003] In starch-based gel-coated slow-release fertilizers, polyacrylic acid (PAA) easily combines with protons in the solution or ionizes protons. At low pH values, -COOH is easily protonated, and hydrophobicity plays a dominant role, causing the polymer chains containing carboxyl groups to curl, making the pore size of the membrane surface larger, which is conducive to the passage of the permeable medium; at high pH values, -COOH is ionized into -COO-, making the polymer chains stretch, the pore size smaller, and the permeable medium difficult to pass through. From the above characteristics, it can be seen that the gel has the potential to be used as a coating material for pH-responsive slow-release fertilizers. However, in the prior art, there is little research on starch-based hydrogels with pH responsiveness, and it is impossible to know the water absorption and swelling properties of the gel, the pH responsiveness, and the water retention and controlled release properties of the fertilizer in environments with different pH values, which seriously restricts its development as a coating material for slow-release fertilizers. Based on this, the present invention designs a pH-responsive starch-based gel-coated slow-release fertilizer to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a pH-responsive starch-based gel-coated slow-release fertilizer, which solves the problem that there is little research on pH-responsive starch-based hydrogels in the background art and that the development of slow-release fertilizer coating materials is restricted.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A pH-responsive starch-based gel-coated slow-release fertilizer comprises a core fertilizer and a pH-responsive starch-based gel coating coated on the surface of the core fertilizer, wherein the core fertilizer is urea, and the coating material is prepared by cross-linking polymerization of amorphous starch, acrylic acid (AA) monomer, cross-linking agent N,N'-methylenebisacrylamide (MBA) and initiator potassium persulfate (KPS), and the coating material exhibits different permeabilities at different pH values ​​to control the release rate of nutrients.

[0007] Preferably, the method for preparing the amorphous starch comprises:

[0008] Step S101, adding common corn starch into 50% by volume ethanol, and stirring at 85° C.;

[0009] Step S102, obtaining amorphous starch through suction filtration, washing, drying, crushing and screening.

[0010] Preferably, the method for preparing the pH responsive starch-based gel comprises the following steps:

[0011] Step S201, dissolving amorphous starch in distilled water, adding acrylic acid (AA) and a crosslinking agent N,N'-methylenebisacrylamide (MBA), and performing a pre-crosslinking treatment at 60° C. for 30 minutes;

[0012] Step S202, slowly dripping an initiator solution containing potassium persulfate (KPS) dissolved in the pre-crosslinking system obtained in the previous step, heating the system to initiate a crosslinking reaction, and obtaining a gel;

[0013] Step S203, drying the obtained gel and grinding it into powder for later use.

[0014] Preferably, in the cross-linking reaction in step S202, the molar ratio of amorphous starch (St) to acrylic acid (AA) ranges from 2:1 to 7:2, the molar ratio of amorphous starch (St) to cross-linking agent N,N'-methylenebisacrylamide (MBA) ranges from 300:1 to 2000:1, and the molar ratio of amorphous starch (St) to potassium persulfate (KPS) is fixed at 400:1.

[0015] Preferably, the method for preparing the coated slow-release fertilizer comprises:

[0016] Anhydrous ethanol is sprayed on the surface of urea to wet it, and then the ground pH-responsive starch-based gel powder is evenly coated on the surface of urea using a disc method, and the powder is dried after coating multiple layers.

[0017] Preferably, the number of coating layers is three, the drying temperature is 50° C., and the drying time is 48 hours.

[0018] Preferably, the pH-responsive starch-based gel-coated slow-release fertilizer comprises the following steps:

[0019] Step a, preparing amorphous starch;

[0020] Step b. using amorphous starch as a base material to prepare a pH-responsive starch-based gel through a cross-linking reaction;

[0021] Step c, after the surface of the core fertilizer is uniformly moistened, the pH-responsive starch-based gel coating powder is uniformly coated on the surface of the core fertilizer by a disc method to form a multi-layer coating;

[0022] Step d, drying and curing at a certain temperature to obtain a pH-responsive starch-based gel-coated slow-release fertilizer.

[0023] Preferably, the raw material ratios, reaction conditions and operation details in the above steps are optimized to ensure that the prepared fertilizer has good pH responsiveness and slow-release effect.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] 1. The present invention converts ordinary corn starch into amorphous starch through a specific preparation process, and successfully cross-links it with acrylic acid (AA) monomer and cross-linking agent N,N'-methylenebisacrylamide (MBA) to form a pH-responsive starch-based gel with a three-dimensional network structure. This gel can intelligently adjust its permeability according to changes in soil pH, thereby promoting rapid nutrient release in acidic soils and slowing down nutrient release in alkaline soils, thereby significantly improving the pH responsiveness of the fertilizer.

[0026] 2. The pH-responsive starch-based gel-coated slow-release fertilizer (SA-SRF) of the present invention exhibits good water holding rate and water retention rate in soil environments with different pH values, especially in alkaline soils, which helps to improve soil water retention capacity, reduce irrigation requirements, and promote crop growth.

[0027] 3. The SA-SRF of the present invention exhibits excellent slow-release performance in a weakly alkaline soil environment, and the cumulative release rate of nitrogen balance is stable and meets the slow-release fertilizer standard. This slow-release characteristic helps to reduce nutrient loss, improve fertilizer utilization, reduce environmental pollution, and meet the nutrient needs of crops at different growth stages. By intelligently regulating the nutrient release rate, the slow-release fertilizer can ensure that nutrients are released slowly and steadily when crops need them most, thereby improving the overall utilization of fertilizers. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A method for preparing a pH-responsive starch-based gel-coated slow-release fertilizer;

[0029] Figure 2 The detailed process of preparing pH-responsive starch-based gel-coated slow-release fertilizer;

[0030] Figure 3 The formula diagram of pH-responsive starch-based gel (SA);

[0031] Figure 4Amorphous starch (Aa), SA (Ab), different St to AA molar ratios (B) and

[0032] FTIR spectra of starch-based gels with different molar ratios of St to MBA (C);

[0033] Figure 5 For starch (Aa), amorphous starch (Ab), different molar ratios of St and AA

[0034] XRD patterns of starch-based gels with different molar ratios of St and MBA;

[0035] Figure 6 SEM images of SA gels with St to AA molar ratios of 2:1 (a, b), 3:1 (c, d), 7:2 (e, f), 4:1 (g, h), and 5:1 (i, j) at different scales;

[0036] Figure 7 SEM images of SA gels with St:MBA molar ratios of 300:1 (a, b, c, d), 500:1 (e, f, g, h), 1000:1 (i, j, k, l), 1500:1 (m, n, o, p), and 2000:1 (q, r, s, t) at different scales;

[0037] Figure 8 The graphs are the changing trends of water absorption swelling ratio (A), equilibrium swelling ratio (B) and swelling equilibrium time (C) of SA gels with different molar ratios of St to AA;

[0038] Fig. 9 The graphs are the changing trends of water absorption swelling ratio (A), equilibrium swelling ratio (B) and swelling equilibrium time (C) of SA gels with different molar ratios of St to MBA;

[0039] Fig.10 The change trend diagram of water absorption swelling rate (a, d, g, j, m), equilibrium swelling rate (b, e, h, k, n) and swelling equilibrium time (c, f, i, l, o) of SA gel with different St to MBA molar ratio at different pH;

[0040] Fig.11 The pH responsiveness trend diagram of SA gel with different molar ratios of St and AA;

[0041] Fig.12 The reaction trend diagrams of water absorption swelling rate (a, d, g, j, m), equilibrium swelling rate (b, e, h, k, n) and swelling equilibrium time (c, f, i, l, o) of SA gels with different St to MBA molar ratios at different pH values;

[0042] Fig.13The pH responsiveness trend diagram of SA gel with different molar ratios of St and MBA;

[0043] Fig.14 is the water holding performance diagram of SA-SRF in soil;

[0044] Fig.15 is the water retention performance diagram of SA-SRF in soil;

[0045] Fig.16 This is the controlled release performance diagram of SA-SRF in water;

[0046] Fig.17 This is the controlled release performance diagram of SA-SRF in soil;

[0047] Fig.18 This is a data table of the slow-release performance of SNA-SRF in soil. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Embodiment 1;

[0050] In an embodiment of the present invention, a pH-responsive starch-based gel-coated slow-release fertilizer comprises a core fertilizer and a pH-responsive starch-based gel coating coated on the surface of the core fertilizer, wherein the core fertilizer is urea, and the coating material is prepared by cross-linking polymerization of amorphous starch, acrylic acid (AA) monomer, cross-linking agent N,N'-methylenebisacrylamide (MBA) and initiator potassium persulfate (KPS), and the coating material exhibits different permeabilities at different pH values ​​to control the release rate of nutrients.

[0051] The preparation method of amorphous starch comprises:

[0052] Step S101, adding common corn starch into 50% by volume ethanol, and stirring at 85° C.;

[0053] Step S102, obtaining amorphous starch through suction filtration, washing, drying, crushing and screening.

[0054] The preparation method of pH responsive starch-based gel comprises the following steps:

[0055] Step S201, dissolving amorphous starch in distilled water, adding acrylic acid (AA) and a crosslinking agent N,N'-methylenebisacrylamide (MBA), and performing a pre-crosslinking treatment at 60° C. for 30 minutes;

[0056] Step S202, slowly dripping an initiator solution containing potassium persulfate (KPS) dissolved in the pre-crosslinking system obtained in the previous step, heating the system to initiate a crosslinking reaction, and obtaining a gel;

[0057] Step S203, drying the obtained gel and grinding it into powder for later use.

[0058] In the cross-linking reaction in step S202, the molar ratio of amorphous starch (St) to acrylic acid (AA) ranges from 2:1 to 7:2, the molar ratio of amorphous starch (St) to cross-linking agent N,N'-methylenebisacrylamide (MBA) ranges from 300:1 to 2000:1, and the molar ratio of amorphous starch (St) to potassium persulfate (KPS) is fixed at 400:1.

[0059] The preparation method of the coated slow-release fertilizer comprises:

[0060] Anhydrous ethanol is sprayed on the surface of urea to wet it, and then the ground pH-responsive starch-based gel powder is evenly coated on the surface of urea using a disc method, and the powder is dried after coating multiple layers.

[0061] The number of coating layers is three, the drying temperature is 50° C., and the drying time is 48 hours.

[0062] A pH-responsive starch-based gel-coated slow-release fertilizer comprises the following steps:

[0063] Step a, preparing amorphous starch;

[0064] Step b. using amorphous starch as a base material to prepare a pH-responsive starch-based gel through a cross-linking reaction;

[0065] Step c, after the surface of the core fertilizer is uniformly moistened, the pH-responsive starch-based gel coating powder is uniformly coated on the surface of the core fertilizer by a disc method to form a multi-layer coating;

[0066] Step d, drying and curing at a certain temperature to obtain a pH-responsive starch-based gel-coated slow-release fertilizer.

[0067] The raw material ratios, reaction conditions and operation details in the above steps are optimized to ensure that the prepared fertilizer has good pH responsiveness and slow-release effect.

[0068] The working principle of the embodiment of the present invention is: ordinary corn starch is converted into amorphous starch through a specific preparation process. This process involves high-temperature stirring treatment in an ethanol solution, followed by filtration, washing, drying, and crushing and screening, aiming to change the crystalline structure of the starch, increase its reactivity and hydrophilicity, and provide a basis for subsequent cross-linking reactions.

[0069] Amorphous starch is used as a base material, pre-crosslinked with acrylic acid (AA) monomer and crosslinker N,N'-methylenebisacrylamide (MBA), and then potassium persulfate (KPS) is added as an initiator to initiate a crosslinking polymerization reaction to form a pH-responsive starch-based gel with a three-dimensional network structure. In this process, the molar ratio of amorphous starch to acrylic acid and crosslinker is carefully controlled to ensure that the gel can show different permeabilities under different pH environments, thereby realizing intelligent regulation of nutrient release rate.

[0070] The prepared pH-responsive starch-based gel is dried and ground into powder, and evenly coated on the surface of urea (core fertilizer) by the disc method to form a multi-layer coating structure. This coating structure can not only effectively protect the core fertilizer from the influence of the external environment, but also intelligently adjust the release rate of nutrients according to changes in soil pH. In acidic soils, the permeability of the coating increases, promoting the rapid release of nutrients to meet crop needs; in alkaline soils, the permeability of the coating decreases, slowing down the release of nutrients and avoiding nutrient loss and waste.

[0071] By drying and curing at a certain temperature, the coating layer is tightly attached to the surface of the core fertilizer to form a stable and long-lasting slow-release fertilizer structure. The raw material ratio, reaction conditions and operating details in the entire preparation process are optimized to ensure that the prepared fertilizer has good pH responsiveness and slow-release effect, thereby improving the utilization rate of the fertilizer, reducing environmental pollution and promoting sustainable agricultural development.

[0072] Embodiment 2;

[0073] 1. FTIR characterization analysis of SA

[0074] like Figure 4 As shown, the FTIR analysis results of SA gels with amorphous starch (Aa), SA (Ab), St and AA molar ratios of 2:1 (Ba), 3:1 (Bb), 4:1 (Bc), 5:1 (Bd) and St and MBA molar ratios of 300:1 (Ca), 500:1 (Cb), 1000:1 (Cc), 1500:1 (Cd), 2000:1 (Ce). 3200-3400 cm in curve Aa -1 It is the stretching vibration absorption peak of the hydroxyl (-OH) on the starch molecular chain, 2900cm -1is the stretching vibration absorption peak of methylene (-CH2-) in starch, 1650cm -1 is the stretching vibration absorption peak of the carbonyl (C=O) in starch, 1400cm -1 It is the stretching vibration absorption peak of the carbon-hydrogen bond (CH) in starch. 2820cm in curve Ab -1 is the stretching vibration absorption peak of the hydroxyl group (-OH) in AA, 1650cm -1 The increase in the intensity of the peak at 1400 cm is due to the synergistic effect of the carbonyl (C=O) in AA and the carbonyl (C=O) in starch, while -1 The characteristic absorption peak at 2820cm is enhanced due to the antisymmetric and stretching vibration of the carboxyl C=O in AA. -1 、1650cm -1 and 1400cm -1 The existence of the peak at fully demonstrates that SA has been successfully prepared.

[0075] like Figure 4 As shown in B, with the increase of St content, the SA gel 2820cm -1 、1650cm -1 、1400cm -1 and 780cm -1 The intensity of the peak at 1650cm increases first and then decreases, reaching a maximum value when the molar ratio of St to AA is 4:1 (Bc). -1 The intensity of the peak decreases first and then increases, reaching the minimum value when the molar ratio of St to MBA is 1000:1.

[0076] 2. XRD characterization analysis of SA

[0077] like Figure 5As shown in the figure, XRD was used to characterize the crystal structure of SA gel of starch (Aa), amorphous starch (Ab), St and AA molar ratio of 2:1 (Ba), 3:1 (Bb), 7:2 (Bc), 4:1 (Bd), 5:1 (Be) and St and MBA molar ratio of 300:1 (Ca), 500:1 (Cb), 1000:1 (Cc), 1500:1 (Cd), 2000:1 (Ce). In curve Aa, the diffraction peaks of starch appeared at 2θ of 18.2°, 22.6°, 34.2° and 81.3°. The baseline of the spectrum was not stable, the diffraction peaks were relatively thin and high in intensity, and there were many sharp peaks between 10° and 25°, which may come from the impurities in the starch. The baseline of the spectrum in curve Ab is relatively stable, and the diffraction peaks at 18.2°, 22.6°, and 34.2° are relatively wide and weak, indicating that the crystallinity of amorphous starch is lower than that of starch, and the gel prepared with amorphous starch as raw material will have a higher degree of cross-linking. Compared with the XRD spectrum of amorphous starch, SA gel only has a wider and blunter single peak between 2θ of 10° and 25°, the baseline of the spectrum is relatively stable, and the impurity components have obviously disappeared.

[0078] With the gradual increase of St content, the intensity of the peak of SA gel only at 2θ between 10° and 25° first increases and then decreases, and the crystallinity of SA gel with a St to AA molar ratio of 7:2 is the lowest.

[0079] 3. SEM Characterization Analysis of SA

[0080] Figure 6 SEM images of SA gels at different scales with St to AA molar ratios of 2:1 (a, b), 3:1 (c, d), 7:2 (e, f), 4:1 (g, h), and 5:1 (i, j) are shown. When the molar ratio of St to AA is 2:1 (a, b), there is a large area of ​​gel skeleton wall in the gel, the gel skeleton is coarse, the number of pores is small, and the pore diameter is small. When the molar ratio of St to AA is 3:1 (c, d), there is still a large area of ​​gel skeleton wall in the gel, and the skeleton wall thickness is about 10 μm, but its pore diameter begins to increase. When the molar ratio of St to AA is 7:2 (e, f), the number of pores increases significantly, the pore diameter is between 20-40 μm, and the thickness of the gel skeleton wall decreases, and the thickness is between 5-8 μm. When the molar ratio of St to AA is 4:1 (g, h), the pore diameter increases to between 30-50μm, and the thickness of the gel skeleton wall decreases to below 5μm, but the number of pores decreases, forming "capsules". When the molar ratio of St to AA is 5:1 (i, j), the pore diameter remains between 30-50μm, the thickness of the gel skeleton wall remains below 5μm, and the area of ​​the skeleton wall shows a trend of expansion.

[0081] With the gradual increase of St content, the pore diameter of SA gel gradually increases and remains between 30-50 μm. The number of pores first increases and then decreases, reaching the maximum value when the molar ratio of St to AA is 7:2.

[0082] Figure 7 The SEM images of SA gels at different scales with St to MBA molar ratios of 300:1 (a, b, c, d), 500:1 (e, f, g, h), 1000:1 (i, j, k, l), 1500:1 (m, n, o, p), and 2000:1 (q, r, s, t) are shown. When the molar ratio of St to MBA is 300:1 (a, b, c, d), the gel exhibits a dense three-dimensional network structure, with a fine gel skeleton and a small pore diameter controlled between 5-10 μm. The number of pores is large and the arrangement is uniform and dense. When the molar ratio of St to MBA is 500:1 (e, f, g, h), the gel pore diameter increases to between 10-25 μm, the gel skeleton begins to thicken, and the width increases to 10 μm. When the molar ratio of St to MBA is 1000:1 (i, j, k, l), the gel pore diameter increases to between 25-40 μm, and the gel skeleton width increases to between 12-15 μm. When the molar ratio of St to MBA is 1500:1 (m, n, o, p), the gel pore diameter increases to between 30-50 μm, and the gel skeleton width remains between 12-15 μm. When the molar ratio of St to MBA is 2000:1 (q, r, s, t), the gel pore diameter increases to between 70-100 μm, and the gel skeleton width increases to 20 μm.

[0083] With the increase of MBA content, the pore diameter and gel skeleton width of SA gel gradually decrease, the number of pores gradually increases, the density of the gel becomes higher and higher, and its water absorption and swelling properties will gradually increase.

[0084] The working principle of the embodiment of the present invention is: when preparing pH-responsive starch-based gel, amorphous starch, acrylic acid (AA) monomer and cross-linking agent N, N'-methylenebisacrylamide (MBA) are pre-cross-linked, and a cross-linking reaction is triggered by potassium persulfate (KPS) to form a gel with a three-dimensional network structure. In this process, the molar ratio of amorphous starch to AA and the amount of MBA significantly affect the permeability and structural properties of the gel. As the molar ratio of St to AA increases, the number and diameter of the pores of the gel first increase and then decrease, reaching the optimum at a specific ratio. At the same time, the amount of MBA also regulates the cross-linking density and pore structure of the gel. When the MBA content is low, the gel pores are larger and the skeleton is coarser; when the MBA content increases, the gel structure is denser, the number of pores increases and the diameter decreases.

[0085] The pH-responsive starch-based gel powder is evenly coated on the surface of urea to form a multi-layer coated slow-release fertilizer. The coating material exhibits different permeabilities at different pH values, thereby controlling the release rate of nutrients. In an acidic or alkaline environment, the swelling degree and permeability of the gel will change, which in turn affects the release rate of nutrients. When the soil pH changes, the permeability of the gel is adjusted accordingly, ensuring that nutrients are released slowly and steadily when crops need them most, improving fertilizer utilization and reducing environmental pollution.

[0086] FTIR analysis confirmed that amorphous starch and AA were successfully cross-linked to form SA gel with specific functional groups. XRD analysis revealed the change in gel crystallinity, further proving the occurrence of cross-linking reaction and its effect on gel structure. SEM images intuitively showed the pore structure and skeleton morphology of the gel. Different molar ratios of St to AA and MBA significantly affected the pore diameter, number and skeleton wall thickness of the gel. These structural characteristics are directly related to the permeability and sustained release performance of the gel.

[0087] Embodiment 3;

[0088] 1. Study on the water absorption and swelling properties of SA

[0089] In the embodiment of the present invention, the water absorbent having a three-dimensional network structure formed by cross-linking a polymer containing hydrophilic groups such as hydroxyl and carboxyl groups has the function of absorbing and retaining a large amount of water, and can effectively improve the absorption and slow release of trace elements in crops. In the study of this chapter, the swelling behavior was measured using a single factor experiment, and the molar ratio of St to AA and the molar ratio of St to MBA were optimized. The equilibrium swelling of all prepared SNA hydrogels was studied in a water environment at room temperature and pH = 7, and the water absorption swelling rate of the samples was measured every 5 hours.

[0090] (1) Effect of the molar ratio of St to AA on the water absorption and swelling properties of SA

[0091] Figure 8 The water absorption swelling ratio (A), equilibrium swelling ratio (B) and swelling equilibrium time (C) of SA gels with St to AA molar ratios of 2:1, 3:1, 7:2, 4:1 and 5:1 are shown. Figure 8In A, the water absorption swelling rate of SA gels with different St to AA molar ratios gradually increased with the increase of time, and reached swelling equilibrium after a certain period of time. The SNA gel with a St to AA molar ratio of 3:1 reached swelling equilibrium the fastest, with a swelling equilibrium time of 30h, but its equilibrium swelling rate was 7.71g / g, which was due to the large pores of the gel and the fast adsorption of water molecules. The SA gel with a St to AA molar ratio of 2:1 showed the largest equilibrium swelling rate (7.85g / g) and swelling equilibrium time (110h), which was due to the addition of AA, which increased the hydrophilicity of the gel and gave it better water absorption and swelling properties. The SA gels with St to AA molar ratios of 7:2, 4:1 and 5:1 reached swelling equilibrium at 40h, 75h and 65h, respectively, and their equilibrium swelling rates were 6.34g / g, 5.70g / g and 5.98g / g, respectively.

[0092] The water absorption swelling ratio of SA gel gradually decreases according to the following molar ratio of St to AA: St:AA=2:1>St:AA=3:1>St:AA=7:2>St:AA=5:1>St:AA=4:1.

[0093] (2) Effect of the molar ratio of St to MBA on the water absorption and swelling properties of SA

[0094] Fig. 9 The water absorption swelling ratio (A), equilibrium swelling ratio (B) and swelling equilibrium time (C) of SA gels with St to MBA molar ratios of 300:1, 500:1, 1000:1, 1500:1 and 2000:1 are shown. Fig. 9 As shown in Figure A, the water absorption swelling rate of SA gels with different St to MBA molar ratios gradually increases with time and reaches swelling equilibrium after a certain period of time. The SA gel with a St to MBA molar ratio of 2000:1 reaches swelling equilibrium the fastest, with a swelling equilibrium time of 45h and a balanced swelling rate of 6.79g / g. This is because when the MBA content is too low, the gel crosslinking degree is small and the pore diameter is large. The SA gel with a St to MBA molar ratio of 500:1 has the largest equilibrium swelling rate (6.91g / g) and the longest swelling equilibrium time (75h).

[0095] The water absorption swelling ratio of SA gel gradually decreases according to the following molar ratio of St to MBA: St:MBA=500:1>St:MBA=300:1>St:MBA=2000:1>St:MBA=1000:1>St:MBA=1500:1.

[0096] 2. Study on pH response performance of SA

[0097] In this patent, the pH response performance of SA gel is mainly tested by the swelling equilibrium rate of the gel at different pH values. The equilibrium swelling of all prepared SNA hydrogels is studied in water environments of pH=3, pH=5, pH=7, pH=9, and pH=11, and the water absorption swelling rate of the samples is measured every 5 hours.

[0098] (1) Effect of the molar ratio of St to AA on the pH response of SA gel

[0099] Fig.10 The water absorption swelling rate, equilibrium swelling rate and swelling equilibrium time of SA gels with St to AA molar ratio of 2:1 (a, b, c), 3:1 (d, e, f), 7:2 (g, h, i), 4:1 (j, k, l) and 5:1 (m, n, o) in water environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 are shown. The SA gel with St to AA molar ratio of 2:1 reaches swelling equilibrium fastest in water environment of pH = 11, with a swelling equilibrium time of 70h, and shows the lowest equilibrium swelling rate (5.92g / g); it shows the longest swelling equilibrium time (110h) in water environments of pH = 7 and pH = 9, and its equilibrium swelling rate is also similar, which is 7.85g / g and 7.93g / g respectively. The SA gel with a St to AA molar ratio of 3:1 quickly reached swelling equilibrium in a water environment with a pH of 7, with a swelling equilibrium time of 30 h, and showed the lowest equilibrium swelling rate (7.71 g / g); it also showed the highest equilibrium swelling rate (7.92 g / g) and the longest swelling equilibrium time (55 h) in a water environment with a pH of 7. The SA gel with a St to AA molar ratio of 7:2 reached swelling equilibrium most quickly in a water environment with a pH of 7, with a swelling equilibrium time of 40 h, and showed the highest equilibrium swelling rate (6.34 g / g); it showed the longest swelling equilibrium time (65 h) in a water environment with a pH of 11. The SA gel with a molar ratio of St to AA of 4:1 reached swelling equilibrium most quickly in a water environment of pH=3, with a swelling equilibrium time of 55h, and showed the lowest equilibrium swelling rate (5.13g / g); it showed the highest equilibrium swelling rate (6.28g / g) in a water environment of pH=5; and it showed the longest swelling equilibrium time (85h) in a water environment of pH=11. The SA gel with a molar ratio of St to AA of 5:1 reached swelling equilibrium most quickly in a water environment of pH=3, with a swelling equilibrium time of 25h, and showed the lowest equilibrium swelling rate (4.93g / g); it showed the highest equilibrium swelling rate (5.98g / g) in a water environment of pH=7; and it showed the longest swelling equilibrium time (80h) in a water environment of pH=11.

[0100] Fig.11The pH responsiveness of SA gels with St to AA molar ratios of 2:1, 3:1, 7:2, 4:1, and 5:1 is shown. Fig.11 As shown in Figure A, the equilibrium swelling of SA gels with St to AA molar ratios of 2:1 and 5:1 first increases and then decreases as the pH value gradually increases, showing good water absorption and swelling properties in neutral and weakly alkaline water environments. Fig.11 As shown in Figure B, the pH response curves of SA gels with St to AA molar ratios of 3:1 and 7:2 have completely opposite changing trends, among which the SA gel with a St to AA molar ratio of 3:1 exhibits better water absorption and swelling properties in all pH solutions.

[0101] (2) pH responsiveness of SA gels with different St:AA molar ratios

[0102] Fig.12The water absorption swelling rate, equilibrium swelling rate and swelling equilibrium time of SA gels with St to MBA molar ratios of 300:1 (a, b, c), 500:1 (d, e, f), 1000:1 (g, h, i), 1500:1 (j, k, l) and 2000:1 (m, n, o) in water environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 are shown. SA gels with a St to MBA molar ratio of 300:1 quickly reach swelling equilibrium in water environments of pH = 5 and pH = 7, with a swelling equilibrium time of 65 h, and show similar equilibrium swelling rates of 6.84 g / g and 6.78 g / g, respectively; they show the highest equilibrium swelling rate (7.25 g / g) in water environments of pH = 11; and they show the longest swelling equilibrium time (80 h) in water environments of pH = 9. The SA gel with a molar ratio of St to MBA of 500:1 reached swelling equilibrium most quickly in a water environment with a pH of 3, with a swelling equilibrium time of 70 h and a balanced swelling rate of 6.54 g / g; it showed the highest equilibrium swelling rate (7.18 g / g) in a water environment with a pH of 5; and it showed the longest swelling equilibrium time (85 h) in a water environment with a pH of 11. The SA gel with a molar ratio of St to MBA of 1000:1 reached swelling equilibrium most quickly in a water environment with a pH of 3, with a swelling equilibrium time of 55 h, and it showed the lowest equilibrium swelling rate (5.13 g / g); it showed the highest equilibrium swelling rate (6.28 g / g) in a water environment with a pH of 5; and it showed the longest swelling equilibrium time (85 h) in a water environment with a pH of 11. The SA gel with a St to MBA molar ratio of 1500:1 reached swelling equilibrium most quickly in a water environment of pH=3, with a swelling equilibrium time of 45h and a balanced swelling rate of 5.25g / g; it showed the highest equilibrium swelling rate (5.94g / g) in a water environment of pH=5; and it showed the longest swelling equilibrium time (80h) in a water environment of pH=9. The SA gel with a St to MBA molar ratio of 2000:1 reached swelling equilibrium most quickly in a water environment of pH=7, with a swelling equilibrium time of 45h, and it showed the highest equilibrium swelling rate of 6.79g / g; it showed the longest swelling equilibrium time (60h) in water environments of pH=9 and pH=11, and its equilibrium swelling rates were similar, 5.80g / g and 5.62g / g, respectively.

[0103] Fig.13 The pH responsiveness of SA gels with St to MBA molar ratios of 300:1, 500:1, 1000:1, 1500:1 and 2000:1 is shown. Fig.13 As shown in A, the SA gels with St to MBA molar ratios of 300:1 and 2000:1 have completely opposite trends in acidic water environments; in neutral and weak alkaline conditions, the two have the same trend; in strong alkaline environments, the two have opposite trends. Fig.13 As shown in Figure B, the SA gels with St to MBA molar ratios of 500:1, 1000:1 and 1500:1 have similar change trends, gradually increasing in a strong acid environment, gradually decreasing in a weak acid environment, and then gradually leveling off in a neutral and alkaline environment.

[0104] Based on the structural characterization, water absorption and swelling properties and pH response performance results of SA, and taking the alkaline soil environment in the northwest as the application environment, it is necessary to maintain good swelling properties in a weakly alkaline environment. This patent selects SA gel with a molar ratio of St to AA of 3:1 and a molar ratio of St to MBA of 500:1 as the coating material of the fertilizer.

[0105] 3. Water holding and conservation performance of SA-SRF in soils with different pH values

[0106] The soil in the northwest region is alkaline, with less precipitation, low water retention and water holding capacity of sandy soil, and serious soil erosion, which restricts the agricultural development of this region. It is necessary to apply fertilizers with high water retention performance in alkaline soil environment to improve its soil environment.

[0107] (1) Water holding capacity of SA-SRF in soil

[0108] Fig.14 The water holding capacity of 200 g dry soil after adding 0 g and 1 g SA-SRF in a soil environment of pH = 7 (A) and the water holding capacity of 200 g dry soil after adding 1 g SA-SRF in a soil environment of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 (B) are shown. Fig.14 As shown in A, in a pH = 7 environment, after adding 0g and 1g SA-SRF, the water holding rate of 200g dry soil was 46.70% and 50.27% respectively. The water holding rate of the blank group increased by 3.57% after adding 1g SA-SRF. Fig.14 As shown in Figure B, in the soil environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11, after adding 1g of SA-SRF, the water holding rates of 200g of dry soil were 49.98%, 49.95%, 50.27%, 52.46% and 50.45%, respectively, and SA-SRF showed good water holding capacity.

[0109] (2) Water retention performance of SA-SRF in soil

[0110] Fig.15 The figure shows the water retention performance (A) of 200g dry soil after adding 0g and 1g SA-SRF in a soil environment with pH = 7, the water retention performance (B) of 200g dry soil after adding 1g SA-SRF in a soil environment with pH = 7, the water retention rate (C) and the water retention equilibrium time (D). Fig.15As shown in A, in a soil environment with pH = 7, after adding 0g and 1g SA-SRF, the water retention rates of 200g dry soil were 19.17% and 30.29% respectively. The water retention rate of the blank group increased by 11.12% after adding 1g SA-SRF. Fig.15 As shown in B, the period from 0 to 25 days is a rapid water loss period. After 25 days, the water retention rate curves at different pH values ​​gradually reach a plateau. Fig.15 As shown in C and D, in the soil environment of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11, after adding 1g SA-SRF, the water retention rate of 200g dry soil was 25.65%, 26.35%, 30.29%, 33.80% and 31.28%, respectively, and the time to reach the plateau period was 40d, 45d, 45d, 45d and 55d, respectively. Adding SA-SRF can effectively slow down water evaporation and improve the water retention performance of the soil.

[0111] 4. Slow-release performance of SA-SRF in water environments and soils with different pH values

[0112] (1) Water holding capacity of SA-SRF in soil

[0113] Fig.16 The nitrogen release rate of urea and SA-SRF in a pH = 7 water environment (A), the nitrogen release rate of SA-SRF in a pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 water environment (B), the nitrogen equilibrium cumulative release rate (C) and the nitrogen equilibrium release time (D) are shown. Fig.16 As shown in A, in a water environment with pH = 7, pure urea as a blank group was rapidly and completely released within 24 hours, and the nitrogen balance cumulative release rate was 100.00%. SA-SRF nitrogen cumulative release reached equilibrium at 132 hours, and the nitrogen balance cumulative release rate was 83.15%. Fig.16 As shown in B, the nitrogen release curves of SA-SRF in water environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 are rapid release periods from 0 to 72 hours, the nitrogen release rate gradually decreases from 72 to 96 hours, and the nitrogen release curve gradually enters a plateau period after 96 hours, reaching equilibrium. Fig.16 As shown in Figures C and D, the nitrogen balance cumulative release rates of SA-SRF in water environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 were 77.29%, 77.92%, 83.15%, 85.05% and 81.59%, respectively, and the required time was 96h, 120h, 132h, 132h and 144h, respectively. Compared with water environments of pH = 3 and pH = 5, SA-SRF has better sustained-release performance in water environments of pH = 7, pH = 9 and pH = 11.

[0114] (2) Water holding capacity of SA-SRF in soil

[0115] Fig.17 The nitrogen release rate of urea and SA-SRF in a soil environment of pH = 7 (A), the nitrogen release rate of SA-SRF in soil environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 (B), the nitrogen equilibrium cumulative release rate (C) and the nitrogen equilibrium release time (D) are shown. Fig.17 As shown in A, in a soil environment with pH = 7, pure urea as a blank group was rapidly and completely released within 5 days, and the nitrogen balance cumulative release rate was 100.00%. SA-SRF nitrogen cumulative release reached equilibrium at 30 days, and the nitrogen balance cumulative release rate was 78.09%. Fig.17 As shown in B, the nitrogen release curves of SA-SRF in soil environments of pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 are rapid release periods from 0 to 15 days, the nitrogen release rate gradually decreases from 15 to 30 days, and the nitrogen release curve gradually enters a plateau period after 30 days, reaching equilibrium. Fig.17 As shown in C and D, the 5-day cumulative nitrogen release rate of SNA-SRF in soil environments with pH = 3, pH = 5, pH = 7, pH = 9 and pH = 11 was 37.19%, 27.70%, 27.82%, 26.94% and 25.16%, respectively, the 25-day cumulative nitrogen release rate was 74.37%, 69.01%, 74.90%, 69.65% and 65.04%, respectively, and the nitrogen balance cumulative release rate was 74.37%, 74.95%, 78.09%, 80.83% and 79.76%, respectively, and the required time was 15d, 30d, 30d, 35d and 40d, respectively. Compared with the nitrogen balance cumulative release rate of SA-SRF in water, the nitrogen balance cumulative release rate of SA-SRF in soil is less, because the soil environment is more complex than the water environment, and the swelling properties of SA and the slow-release properties of SA-SRF are affected by more factors. The slow-release performance of SA-SRF in soil environments of pH=7, pH=9 and pH=11 meets the national slow-release fertilizer standards.

[0116] The initial nitrogen release rate, 25-day nitrogen cumulative release rate and nitrogen equilibrium cumulative release rate of SA-SRF in soil environments of pH=3, pH=5, pH=7, pH=9 and pH=11 are shown in Fig.18 shown.

[0117] The working principle of the embodiment of the present invention is: according to the FTIR and XRD characterization test results, this patent successfully prepared a starch-based hydrogel SA with pH responsiveness using starch as the base material, AA as the monomer and pH responsive group.

[0118] Based on the structural characterization, water absorption and swelling properties and pH response performance results of SA, and taking the alkaline soil environment in the northwest as the application environment, it is necessary to maintain good swelling properties in a weakly alkaline environment. This patent selects SA gel with a molar ratio of St to AA of 3:1 and a molar ratio of St to MBA of 500:1 as the coating material of the fertilizer.

[0119] In soil environments of pH=3, pH=5, pH=7, pH=9 and pH=11, after adding 1g SA-SRF, the water holding rates of 200g dry soil were 49.98%, 49.95%, 50.27%, 52.46% and 50.45%, respectively, and the water retention rates were 25.65%, 26.35%, 30.29%, 33.80% and 31.28%, respectively. SA-SRF has good water holding and retention properties.

[0120] The nitrogen balance cumulative release rates of SA-SRF in soil environments of pH=7, pH=9 and pH=11 were 78.09%, 80.83% and 79.76%, respectively. Compared with acidic environments, SA-SRF has better slow-release performance in environments of pH=7, pH=9 and pH=11, which meets the application conditions of the alkaline soil environment in the northwest and meets the national slow-release fertilizer standards.

[0121] Working principle: This study successfully prepared SA hydrogels with a three-dimensional network structure by cross-linking polymers containing hydrophilic groups such as hydroxyl and carboxyl groups. These hydrophilic groups not only enhance the hydrophilicity of the hydrogel, but also give it good water absorption and swelling ability. The successful preparation of SA hydrogels and their structural characteristics were verified by characterization methods such as FTIR and XRD.

[0122] In order to optimize the water absorption and swelling properties of SA hydrogel, this study used single factor experiments to explore in detail the effects of the molar ratio of St (probably a monomer, such as styrene) to AA (acrylic acid), and the molar ratio of St to MBA (N,N'-methylenebisacrylamide, as a crosslinker) on the water absorption and swelling properties of the hydrogel. The experimental results show that the combination of a molar ratio of St to AA of 3:1 and a molar ratio of St to MBA of 500:1 exhibits the best water absorption and swelling properties and equilibrium time in a weakly alkaline environment, which is particularly applicable to the alkaline soil environment in the northwest region.

[0123] The pH responsiveness of SA hydrogel was tested by swelling equilibrium rate at different pH values. The experiment found that the molar ratio of St to AA significantly affected the pH responsiveness of the hydrogel. SA gel with a molar ratio of St to AA of 3:1 showed excellent water absorption and swelling performance under various pH environments, especially in weakly alkaline environments. The equilibrium swelling rate of the gel was high, which was conducive to maintaining good swelling performance in alkaline soils in the northwest.

[0124] SA hydrogel was mixed with soil (SA-SRF) to test its water holding and water retention performance in soil environments with different pH values. The experimental results showed that after adding SA-SRF, the water holding and water retention rates of the soil were significantly improved, especially in alkaline soils, where SA-SRF's water holding and water retention performance was even better, which could effectively alleviate the problem of poor soil water retention capacity in the northwest region.

[0125] The nitrogen release performance of SA-SRF in water environments and soils with different pH values ​​was further studied. The results showed that the nitrogen release rate of SA-SRF in weakly alkaline water environments and soils was moderate, and the release process was smooth and long-lasting, meeting the standards of slow-release fertilizers. This slow-release performance helps reduce nutrient loss, improve fertilizer utilization, and thus improve crop growth conditions.

[0126] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit thereof, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A pH-responsive starch-based gel-coated slow-release fertilizer, comprising a core fertilizer and a pH-responsive starch-based gel-coated film coated on the surface of the core fertilizer, characterized in that: The core fertilizer is urea, and the coating material is prepared by cross-linking polymerization of amorphous starch, acrylic acid (AA) monomer, cross-linking agent N,N'-methylenebisacrylamide (MBA) and initiator potassium persulfate (KPS). The coating material exhibits different permeabilities at different pH values ​​to control the release rate of nutrients.

2. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 1, characterized in that: The preparation method of the amorphous starch comprises: Step S101, adding common corn starch into 50% by volume ethanol, and stirring at 85° C.; Step S102, obtaining amorphous starch through suction filtration, washing, drying, crushing and screening.

3. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 1, characterized in that: The preparation method of the pH responsive starch-based gel comprises the following steps: Step S201, dissolving amorphous starch in distilled water, adding acrylic acid (AA) and a crosslinking agent N,N'-methylenebisacrylamide (MBA), and performing a pre-crosslinking treatment at 60° C. for 30 minutes; Step S202, slowly dripping an initiator solution containing potassium persulfate (KPS) dissolved in the pre-crosslinking system obtained in the previous step, heating the system to initiate a crosslinking reaction, and obtaining a gel; Step S203, drying the obtained gel and grinding it into powder for later use.

4. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 3, characterized in that: In the cross-linking reaction in step S202, the molar ratio of amorphous starch (St) to acrylic acid (AA) ranges from 2:1 to 7:2, the molar ratio of amorphous starch (St) to cross-linking agent N,N'-methylenebisacrylamide (MBA) ranges from 300:1 to 2000:1, and the molar ratio of amorphous starch (St) to potassium persulfate (KPS) is fixed at 400:

1.

5. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 1, characterized in that: The preparation method of the coated slow-release fertilizer comprises: Anhydrous ethanol is sprayed on the surface of urea to wet it, and then the ground pH-responsive starch-based gel powder is evenly coated on the surface of urea using a disc method, and the powder is dried after coating multiple layers.

6. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 5, characterized in that: The number of coating layers is three, the drying temperature is 50° C., and the drying time is 48 hours.

7. A pH-responsive starch-based gel-coated slow-release fertilizer according to claim 1, characterized in that: The following steps are involved: Step a, preparing amorphous starch; Step b, using amorphous starch as a base material, preparing a pH-responsive starch-based gel through a cross-linking reaction; Step c, after the surface of the core fertilizer is uniformly moistened, the pH-responsive starch-based gel coating powder is uniformly coated on the surface of the core fertilizer by a disc method to form a multi-layer coating; Step d, drying and curing at a certain temperature to obtain a pH-responsive starch-based gel-coated slow-release fertilizer.

8. The pH-responsive starch-based gel-coated slow-release fertilizer according to claim 1, characterized in that: The raw material ratios, reaction conditions and operation details in the above steps are optimized to ensure that the prepared fertilizer has good pH responsiveness and slow-release effect.

Citation Information

Cited By

  • Water-retention synergistic coated slow-release fertilizer and preparation method thereof

    CN120247602A

  • Starch-based high-water-absorption gel slow-release urea particles and preparation method thereof

    CN120717848A